Peran Sumber Daya Manusia Dalam Meningkatkan Kinerja Sekolah Di Era Digital - Zahra Nabila Iqbal; Ulfa Hayana Sari; Fikri Hamdi Siregar (CV. ITTC INDONESIA, 2024)
In the ever-evolving digital era, the role of human resources (HR) in improving school performance is becoming increasingly crucial. This study aims to analyze how HR, including educators and administrative staff, can contribute effectively in utilizing technology to improve the learning process and school management. The method used in this study is a literature study by collecting data from various sources such as journals and books. The results of the study indicate that training and professional development for teachers and the implementation of a digital-based management system can improve the efficiency and effectiveness of school performance. In addition, collaboration between HR and other stakeholders, such as parents and communities, has also been shown to strengthen support for educational innovation. Thus, good HR management in the digital era not only has an impact on improving the quality of education, but also on achieving the school's strategic goals. This study suggests that schools focus more on developing HR digital competencies as an important step in facing educational challenges in the future.